Intestinal single-pass in situ perfusion technique in rat: the influence of L-carnitine on absorption of 7-methoxytacrine - Kunes, Martin; Svoboda, Zbynĕk; Kvĕtina, Jaroslav; Herout, Vladimír; Herink, Josef; Bajgar, Jirí (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2005)
7-Methoxytacrine (7-MEOTA) is an acetylcholine-esterase inhibitor that is potentially useful in the therapy of some neurodegenerative disorders. L-carnitine (CRT) is a naturally occuring compound that is known to increase penetration of some compounds through biological barriers. Aim of this study was how CRT influenced transintestinal absorption transport 7-MEOTA in rat using single-pass intestinal in situ perfusion method. The rate of absorption of 7-MEOTA during luminal perfusion with single 7-MEOTA was compared with rate of absorption during simultaneous perfusion with 7-MEOTA and CRT and with absorption rate after the premedication with CRT for period of three days before beginning of perfusion. The methodical system was the perfusion of mesenterial bed (from arteria mesenterica superior to vena portae) and intestinal luminal perfusion (from duodenum to ileum). The lower transintestinal absorption in the course of simultaneously administration of CRT than just in case of perfusion with single 7-MEOTA has been found. On the contrary a significantly higher absorption of 7-MEOTA has been noted in group of rats premedicated with CRT for three consecutive days. The interpretation suggested that molecules of CRT incorporated into the metabolism of intestinal cells facilitated transport of 7-MEOTA (as a representative substance which is at least partly transferred by carrier mechanism). In case of simultaneous luminal perfusion with CRT and 7-MEOTA competitive over-saturation of carrier systems is probably.
Keywords: Carnitine; Intestinal Absorption; vitamin B komplex; perfuze; krysa rodu Rattus; takrin; Cholinesterase Inhibitors; Vitamin B Complex; potkani Wistar; Perfusion; Animals; intestinální absorpce; Rats, Wistar; Tacrine; cholinesterasové inhibitory; karnitin; zvířata; Rats